Scientific review committee-an experience from the desk of member-secretary - Misra, Shobha (International Journal of Scientific Reports, 2022)
Writing a proper research proposal is the most important step in conducting a scientific study. Whether the researcher intends to submit the proposal to an ethical committee, research body or funding organization, it is vital that the proposal clearly states why the study is planned, how it is proposed to be conducted and the researcher’s commitment to its principles. The current study was carried out to find out common errors committed while submission of research protocol to the scientific review committee (SRC). In 2015, based on feedback and experience of experts in the field and to improve the scientific and technical content of the proposals received, institutional ethical committee for human research was divided into two sub-committees; SRC and institutional ethics committee. This article reports analysis of 100 proposals based on a checklist for submission and discussion during SRC meetings on errors committed. Top ten errors observed were: Incomplete annexure and missing permissions; imprecision and lack of scientific validity in aims and objectives; inappropriate or incomplete statistics; inappropriate; suboptimal instrumentation; lack of clarity on predictor and outcome variables; data collection procedures and analysis lacked completeness; title lacked accuracy and clarity; inappropriate study design; ethical requirements incomplete and sample too small or biased. All errors were reviewed and rectified. Constitution of a separate SRC was found to be effective in providing independent, competent and timely review of all the protocols submitted to it for their scientific merits and feasibility.